Supplementary material 4: Bombus spp trapped in Fairbanks Alaska, 2010 from: Bumble Bees (Hymenoptera: Apidae: Bombus spp.) of Interior Alaska: Species Composition, Distribution, Seasonal Biology, and Parasites - Biodiversity Data Journal 3: e5085 (08 May 2015) https://doi.org/10.3897/BDJ.3.e5085 - Rehanon Pampell; Alberto Pantoja; Derek S. Sikes; Patricia Holloway; Charles Knight; Richard Ranft (Zenodo, 2017)
57 specimens of seven species trapped using Blue Vane pollinator traps with counts of queens, workers, and males by date.